Factors Affecting Attitude Towards Online Shopping: A Case Study Among TVET University Students in The Southern Region of Malaysia - Al-Shameri, Ahmed Saleh Ahmed Saif; Omar, Siti Sarah; Abkar, Mahdi Mohammed Abdullah (Journal of Techno-Social, 2023)
The development of the online shopping in Malaysia is expanding each year as a type of e-commerce, turning to a main concern by the government. Students have been recognized as an important role in building and maintaining this type of shopping. Therefore, the purpose of this study was to identify the factors affecting university students’ attitude towards online shopping. The second objective was to determine the relationship between factors such as quality, prices, saving time, wider selection & trust and the attitude toward online shopping. One variable from the Theory of Planned Behavior (TPB) was adapted in this study. This study followed the quantitative method, utilizing questionnaires for data collection purposes. The respondents of this study were the university students. The data then was analyzed using the Statistical Package for Social Science (SPSS). The findings of this study showed that wider selection of products, saving time, cheaper prices and trust were the most influential factors that affect the students’ attitude towards online shopping. The findings also showed that all the independent variables are correlated with the dependent variable.